The Relationship between Environmental Tobacco Smoke Exposure and Decreased Lung Function in Adolescents : A Comprehensive Systematic Review - Nydia Ayu Ulima; Rajmil Shafira Salsabila (International Medical Journal Corp. Ltd, 2026)
Introduction: Environmental tobacco smoke (ETS) exposure remains a significant public health concern, particularly for adolescents whose lungs are undergoing critical development. Despite declining smoking rates in many countries, millions of adolescents worldwide continue to be exposed to ETS in their homes and communities. This systematic review aims to comprehensively evaluate the relationship between ETS exposure and decreased lung function in adolescents aged 10-19 years. Methods: A systematic review was conducted following established guidelines. Twenty sources were included after screening based on predefined criteria: adolescent population age range (10-19 years), validated ETS exposure measurement, standardized lung function assessment, appropriate observational study design, focus on passive exposure, objective outcome measurement, and general population health status. Data extraction encompassed study characteristics, ETS exposure assessment methods, lung function measures, primary associations, effect sizes, dose-response evidence, effect modifiers, and confounding control. Results: The predominant finding across studies was a negative association between ETS exposure and lung function parameters. Small airway measures (FEF25-75, FEF25) were most consistently affected, with He et al. reporting β = −0.104 (p=0.020) for FEF25-75 growth rate. FEV1 annual growth reduction of −0.34% (95% CI: −0.64% to −0.04%) was documented by Milanzi et al. Dose-response relationships were demonstrated in multiple studies. Critical effect modifiers included sex (girls showing greater vulnerability with FEV1 reduction of −272 ml/s in perinatally exposed females), genetic polymorphisms (β2-adrenoceptor and GSTP1 variants), timing of exposure (prenatal and early childhood windows most critical), and synergistic interactions with active smoking. Discussion: The evidence consistently supports a negative association between ETS exposure and adolescent lung function, with biological plausibility strengthened by acute exposure studies demonstrating immediate effects. Heterogeneity in effect sizes is explained by differences in exposure timing, measurement methods, and population susceptibility. Methodological limitations include variability in confounding control and exposure assessment. Conclusion: ETS exposure is significantly associated with decreased lung function in adolescents, with evidence of dose-response relationships and modification by sex, genetics, and exposure timing. Recommendations include strengthening smoke-free legislation, targeted interventions for vulnerable populations, routine clinical screening, and further research with standardized methodologies.